2005
DOI: 10.1002/ajmg.1320370737
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 21 mosaicism in gonads with unexpectedly high recurrence risks

Abstract: The recurrence risk for Down syndrome (DS) is about 1% in case of a previous offspring with trisomy 21 and minimal in case of a de novo (21;21) translocation. We have monitored 1,211 pregnancies in the first and second trimester after a prior occurrence of trisomy 21. Six couples had a trisomy 21 fetus in a subsequent pregnancy. We studied their lymphocytes, fibroblasts, and in one case ovaries, to detect parental mosaicism for chromosome 21. We detected mosaicism in 2 parents with 3 and 4 pregnancies, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 7 publications
(5 reference statements)
0
14
1
Order By: Relevance
“…Younger couples with three or more conceptions with the same trisomy are good candidates for gonadal mosaicism, as has been clearly demonstrated by several studies (Sachs et al, 1990;Cozzi et al, 1999;Somprasit et al, 2004). Prospective studies on oocytes have also demonstrated that some women have a high risk of producing aneuploid oocytes.…”
Section: Predisposition To Aneuploidymentioning
confidence: 83%
“…Younger couples with three or more conceptions with the same trisomy are good candidates for gonadal mosaicism, as has been clearly demonstrated by several studies (Sachs et al, 1990;Cozzi et al, 1999;Somprasit et al, 2004). Prospective studies on oocytes have also demonstrated that some women have a high risk of producing aneuploid oocytes.…”
Section: Predisposition To Aneuploidymentioning
confidence: 83%
“…Evidence in favour comes from reports of young couples with 3 or more abnormal conceptions with the same chromosome involved in aneuploidy each time [Sachs et al, 1990;Cozzi et al, 1999;Somprasit et al, 2004]. However, the first cytological proof of gonadal mosaicism had to await the development of PGD.…”
Section: Discussionmentioning
confidence: 99%
“…Younger couples with three or more conceptions with the same trisomy are good candidates for gonadal mosaicism, as has been clearly demonstrated by several studies (Sachs et al, 1990;Cozzi et al, 1999;Somprasit et al, 2004). Prospective studies on oocytes using FISH for specifi c chromosomes have also demonstrated that some women have a high risk of producing aneuploid oocytes.…”
mentioning
confidence: 87%